Taxonomy of ‘Euconnus complex’. Part XXIII. Status of Napochus Thomson, Pycnophus Casey, and Filonapochus Franz revisited (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2021)
In previously published parts of this long-term study, subgenera Napochus Thomson and Pycnophus Casey of Euconnus Thomson were tentatively maintained, based on detailed morphological examination of their type species. Since then, many more species have been studied, including several hundred nominal Euconnus s. str., Napochus, and Pycnophus spp., and over a thousand presumably undescribed species collected on all continents. Considering character variability, current diagnoses of Napochus and Pycnophus were found to largely overlap with that of Euconnus s. str., and many species show intermediary features. In the present study, examples of such intermediary or transitional characters are illustrated, and character variability within the Euconnus s. str. + Napochus + Pycnophus morphological group is discussed. Available morphological evidence strongly supports a concept of a highly diverse Euconnus s. str. that includes Napochus and Pycnophus. Consequently, Napochus syn. n. and Pycnophus syn. n. are merged with Euconnus s. str. as junior synonyms. In addition, examination of the type specimens of the type species of Glandularia L.W. Schaufuss and Connophron Casey, both names currently treated as junior synonyms of Napochus, confirms the previously established synonymies. Characters of the previously revised subgenus Filonapochus Franz were also found to fall within the variability revealed in the present study, and also Filonapochus syn. n. is placed as a junior synonym of Euconnus s. str.